Worldwide trends in underweight and obesity from 1990 to 2022: a pooled analysis of 3663 population-representative studies with 222 million children, adolescents, and adults - Nowell H Phelps; Rosie K Singleton; Bin Zhou; Rachel A Heap; Anu Mishra; James E Bennett; Christopher J Paciorek; Victor PF Lhoste; Rodrigo M Carrillo-Larco; Gretchen A Stevens; Andrea Rodriguez-Martinez; Honor Bixby; et al. (The Lancet, 2024)
Underweight and obesity are associated with adverse health outcomes throughout the life course. We estimated the individual and combined prevalence of underweight or thinness and obesity, and their changes, from 1990 to 2022 for adults and school-aged children and adolescents in 200 countries and territories.
Keywords: 330